Comics meets street art in the media cities of the bande dessinée. Examples from Brussels and Geneva - Muranyi, Kata; Maksa, Gyula (Street Art & Urban Creativity, 2023)
Comic media exists in historical and geocultural variations. The historically dynamic identity formation of comic media in some geocultural versions is accompanied by the emergence of mediatic hybridisations that manifest themselves in a street art activity. In this article, we examine these comics-based hybrid media and their use from a media theoretical perspective in the context of two different media cities of the Francophone bande dessinée. In Brussels and Geneva, the institutionalisation of comics has been partially different, but both cities have seen a significant role in hybrid media related to street art. In Brussels, this is the case with comic murals, which have a canonising function and also generate tourist activity. In the case of Geneva, the importance of comic posters and comic-style street signs linked to political communication, civic education, and campaigns by NGOs is striking.